Understanding Climate Change Feedbacks - National Research Council (The National Academies Press, 2003)
During the past decade, scientists have learned much about the complex natural processes that influence climate variability and change, and our ability to model climate has increased significantly. We also have begun to better identify those parts of the climate system that are particularly important and not well understood and that therefore limit our ability to project the future evolution of Earth’s climate. One of these critical areas is our understanding of the role of feedbacks in the climate system and their role in determining climate sensitivity. Feedbacks are processes in the climate system that can either amplify or dampen the system’s response to changed forcings. This study looks at what is known and not known about climate change feedbacks and seeks to identify the feedback processes most in need of improved understanding. It identifies key observations needed to monitor and understand climate feedbacks, discusses ways to evaluate progress in understanding climate feedbacks, recommends ways to improve climate modeling and analysis for climate feedbacks research, and identifies priority areas for research.
Keywords: Earth Sciences; Environment and Environmental Studies

Estimating Climate Sensitivity: Report of a Workshop - National Research Council (The National Academies Press, 2003)
“Climate sensitivity” is a term used to characterize the response of the climate system to an imposed forcing, and is most commonly used to mean the equilibrium global mean surface temperature change that occurs in response to a doubling of atmospheric carbon dioxide concentration. The purpose of this workshop was to explore current capabilities and limitations in quantifying climate sensitivity and consider whether there are alternative approaches for characterizing climate response that might better suit the information needs of policy makers.
Keywords: Environment and Environmental Studies; Earth Sciences

Communicating Uncertainties in Weather and Climate Information: A Workshop Summary - National Research Council (The National Academies Press, 2003)
The report explores how best to communicate weather and climate information by presenting five case studies, selected to illustrate a range of time scales and issues, from the forecasting of weather events, to providing seasonal outlooks, to projecting climate change.
Keywords: Earth Sciences

Fair Weather: Effective Partnership in Weather and Climate Services - National Research Council (The National Academies Press, 2003)
Decades of evolving U.S. policy have led to three sectors providing weather services—NOAA (primarily the National Weather Service [NWS]), academic institutions, and private companies. This three-sector system has produced a scope and diversity of weather services in the United States second to none. However, rapid scientific and technological change is changing the capabilities of the sectors and creating occasional friction. Fair Weather: Effective Partnerships in Weather and Climate Services examines the roles of the three sectors in providing weather and climate services, the barriers to interaction among the sectors, and the impact of scientific and technological advances on the weather enterprise. Readers from all three sectors will be interested in the analysis and recommendations provided in Fair Weather.
Keywords: Earth Sciences; Space and Aeronautics

Planning Climate and Global Change Research: A Review of the Draft U.S. Climate Change Science Program Strategic Plan - National Research Council (The National Academies Press, 2003)
Keywords: Earth Sciences

The Sun to the Earth – and Beyond: Panel Reports - National Research Council (The National Academies Press, 2003)
This volume, The Sun to the Earth-and Beyond: Panel Reports, is a compilation of the reports from five National Research Council (NRC) panels convened as part of a survey in solar and space physics for the period 2003-2013. The NRC's Space Studies Board and its Committee on Solar and Space Physics organized the study. Overall direction for the survey was provided by the Solar and Space Physics Survey Committee, whose report, The Sun to the Earth-and Beyond: A Decadal Research Strategy in Solar and Space Physics, was delivered to the study sponsors in prepublication format in August 2002. The final version of that report was published in June 2003. The panel reports provide both a detailed rationale for the survey committee's recommendations and an expansive view of the numerous opportunities that exist for a robust program of exploration in solar and space physics.
Keywords: Space and Aeronautics

From Climate to Weather: Impacts on Society and Economy - Summary of a Forum, June 28, 2002, Washington, DC (The National Academies Press, 2003)
This report stems from the forum held on June 28, 2002 at the National Academy of Sciences. The objective of the one-day public forum was to discuss the current state of knowledge on the relationship between climate variability and extreme weather and to inform policymakers and other stakeholders on the science and uncertainties associated with floods, tornadoes, hurricanes and other extreme weather events, their link to climate variability, and their societal and economic impacts. Topics discussed by the multidisciplinary participants included the status of scientific understanding on the role of climate change in severe weather events, policy strategies for dealing with these events, the role of Congress in shaping policy regarding extreme events, and the role of the media in educating the public.
Keywords: Earth Sciences

Initial Steps in Rebuilding the Health Sector in East Timor - National Research Council (The National Academies Press, 2003)
In May 2002 Timor Leste (East Timor) emerged as a new nation after centuries of foreign rule and decades of struggle for independence. Its birth was a painful one; a United Nations-brokered Popular Consultation in August 1999, in which an overwhelming majority of the people opted for independence, was followed by several weeks of vengeful violence, looting, and destruction by pro-Indonesia militias. It left the territory and all of its essential services devastated. In this context, the United Nations Transitional Administration in East Timor (UNTAET), with the country's leaders and people and many other partners, set about restoring order and services, building a government structure, and preparing for independence. This paper summarizes the rehabilitation and development of the health sector from early 2000 to the end of 2001.
Keywords: Behavioral and Social Sciences

Satellite Observations of the Earth's Environment: Accelerating the Transition of Research to Operations - National Research Council (The National Academies Press, 2003)
This report addresses the transition of research satellites, instruments, and calculations into operational service for accurately observing and predicting the Earth’s environment. These transitions, which take place in large part between NASA and NOAA, are important for maintaining the health, safety, and prosperity of the nation, and for achieving the vision of an Earth Information System in which quantitative information about the complete Earth system is readily available to myriad users. Many transitions have been ad hoc, sometimes taking several years or even decades to occur, and others have encountered roadblocks—lack of long-range planning, resources, institutional or cultural differences, for instance—and never reached fruition. Satellite Observations of Earth’s Environment recommends new structures and methods that will allow seamless transitions from research to practice.
Keywords: Space and Aeronautics; Earth Sciences

The Sun to the Earth -- and Beyond: A Decadal Research Strategy in Solar and Space Physics - National Research Council (The National Academies Press, 2003)
The sun is the source of energy for life on earth and is the strongest modulator of the human physical environment. In fact, the Sun’s influence extends throughout the solar system, both through photons, which provide heat, light, and ionization, and through the continuous outflow of a magnetized, supersonic ionized gas known as the solar wind. While the accomplishments of the past decade have answered important questions about the physics of the Sun, the interplanetary medium, and the space environments of Earth and other solar system bodies, they have also highlighted other questions, some of which are long-standing and fundamental. The Sun to the Earth—and Beyond organizes these questions in terms of five challenges that are expected to be the focus of scientific investigations in solar and space physics during the coming decade and beyond.
Keywords: Space and Aeronautics

Living on an Active Earth: Perspectives on Earthquake Science - National Research Council (The National Academies Press, 2003)
The destructive force of earthquakes has stimulated human inquiry since ancient times, yet the scientific study of earthquakes is a surprisingly recent endeavor. Instrumental recordings of earthquakes were not made until the second half of the 19th century, and the primary mechanism for generating seismic waves was not identified until the beginning of the 20th century. From this recent start, a range of laboratory, field, and theoretical investigations have developed into a vigorous new discipline: the science of earthquakes. As a basic science, it provides a comprehensive understanding of earthquake behavior and related phenomena in the Earth and other terrestrial planets. As an applied science, it provides a knowledge base of great practical value for a global society whose infrastructure is built on the Earth's active crust. This book describes the growth and origins of earthquake science and identifies research and data collection efforts that will strengthen the scientific and social contributions of this exciting new discipline.
Keywords: Earth Sciences

Leaving Earth: Space Stations, Rival Superpowers, and the Quest for Interplanetary Travel - Robert Zimmerman (The National Academies Press, 2003)
Charged with the ever-present potential for danger and occasionally punctuated by terrible moments of disaster, the history of space exploration has been keenly dramatic. The recent disaster of the Space Shuttle Columbia was a sad but certain reminder that space travel is an extraordinarily dangerous occupation. Oddly enough, it often takes a tragic accident to remind us that we still have a presence in space. In the decades between triumph and tragedy we tend to ignore the fact that there have been scores of space pioneers who have risked their lives to explore our solar system. Indeed, the International Space Station is sometimes referred to as “Alpha,” a moniker that implies that it is our first real permanent presence in space. But this notion is frowned upon by the Russians – and for good reason. Prior to the construction of the controversial International Space Station, a host of daring Russian cosmonauts, and a smaller number of intrepid American astronauts, were living in space for months, some of them for over a year. In this definitive account of man’s quest to become citizens of the cosmos, noted space historian Robert Zimmerman reveals the great global gamesmanship between Russian and American political leaders that drove us to the stars. Beaten to the Moon by their Cold War enemies, the Russians were intent on being first to the planets. They believed that manned space stations held the greatest promise for reaching other worlds and worked feverishly to build a viable space station program – one that would dwarf American efforts and allow the Russians to claim the vast territories of space as their own. Although unthinkable at the time, the ponderously bureaucratic Soviet Union actually managed to overtake the United States in the space station race. Leveraging their propaganda machine and tyrannical politics to launch a series of daring, dangerous, and scientifically brilliant space exploits, their efforts not only put them far ahead of NASA, they also helped to reshape their own society, transforming it from dictatorship to democracy. At the same time, the American space program at NASA was also evolving, but not necessarily for the better. In fact, the two programs were slowly but inexorably trading places. Drawing on his vast store of knowledge about space travel, as well as hundreds of interviews with cosmonauts, astronauts, and scientists, Zimmerman has superbly captured the excitement and suspense of our recent space-traveling past. For space and history enthusiasts alike, Leaving Earth describes a rich heritage of adventure, exploration, research, and discovery.
Keywords: Explore Science; Space and Aeronautics

Fulfilling the Potential of Cancer Prevention and Early Detection - Institute of Medicine; National Research Council (The National Academies Press, 2003)
Cancer ranks second only to heart disease as a leading cause of death in the United States, making it a tremendous burden in years of life lost, patient suffering, and economic costs. Fulfilling the Potential for Cancer Prevention and Early Detection reviews the proof that we can dramatically reduce cancer rates. The National Cancer Policy Board, part of the Institute of Medicine, outlines a national strategy to realize the promise of cancer prevention and early detection, including specific and wide-ranging recommendations. Offering a wealth of information and directly addressing major controversies, the book includes: A detailed look at how significantly cancer could be reduced through lifestyle changes, evaluating approaches used to alter eating, smoking, and exercise habits. An analysis of the intuitive notion that screening for cancer leads to improved health outcomes, including a discussion of screening methods, potential risks, and current recommendations. An examination of cancer prevention and control opportunities in primary health care delivery settings, including a review of interventions aimed at improving provider performance. Reviews of professional education and training programs, research trends and opportunities, and federal programs that support cancer prevention and early detection. This in-depth volume will be of interest to policy analysts, cancer and public health specialists, health care administrators and providers, researchers, insurers, medical journalists, and patient advocates.
Keywords: Health and Medicine

Assessment of NASA's Draft 2003 Earth Science Enterprise Strategy: Letter Report (The National Academies Press, 2003)
Keywords: Space and Aeronautics; Earth Sciences

Describing Death in America: What We Need to Know: Executive Summary - Institute of Medicine; National Research Council (The National Academies Press, 2003)
National expenditures for medical care in the months and days preceding death are enormous. But we do not know whether that money is buying good quality care or optimizing the quality of life of those dying, or whether the situation is getting better or worse over time. The information that exists “describing death” at a national level – though some of it is very informative – is fragmentary. This report recommends ways to fill the information gaps by better use of existing nationally-representative data, and through some new measures, in particular, a new, ongoing National Mortality Followback Survey. The aim is to allow us to benchmark where we are today as a society, and what goals we can set to minimize pain and suffering and maximize the quality of life of all of us who will die in the years to come.
Keywords: Health and Medicine

The Future of the Public's Health in the 21st Century - Institute of Medicine (The National Academies Press, 2003)
The anthrax incidents following the 9/11 terrorist attacks put the spotlight on the nation's public health agencies, placing it under an unprecedented scrutiny that added new dimensions to the complex issues considered in this report. The Future of the Public's Health in the 21st Century reaffirms the vision of Healthy People 2010, and outlines a systems approach to assuring the nation's health in practice, research, and policy. This approach focuses on joining the unique resources and perspectives of diverse sectors and entities and challenges these groups to work in a concerted, strategic way to promote and protect the public's health. Focusing on diverse partnerships as the framework for public health, the book discusses: The need for a shift from an individual to a population-based approach in practice, research, policy, and community engagement. The status of the governmental public health infrastructure and what needs to be improved, including its interface with the health care delivery system. The roles nongovernment actors, such as academia, business, local communities and the media can play in creating a healthy nation. Providing an accessible analysis, this book will be important to public health policy-makers and practitioners, business and community leaders, health advocates, educators and journalists.
Keywords: Health and Medicine

Health Professions Education: A Bridge to Quality - Institute of Medicine (The National Academies Press, 2003)
The Institute of Medicine study Crossing the Quality Chasm (2001) recommended that an interdisciplinary summit be held to further reform of health professions education in order to enhance quality and patient safety. Health Professions Education: A Bridge to Quality is the follow up to that summit, held in June 2002, where 150 participants across disciplines and occupations developed ideas about how to integrate a core set of competencies into health professions education. These core competencies include patient-centered care, interdisciplinary teams, evidence-based practice, quality improvement, and informatics. This book recommends a mix of approaches to health education improvement, including those related to oversight processes, the training environment, research, public reporting, and leadership. Educators, administrators, and health professionals can use this book to help achieve an approach to education that better prepares clinicians to meet both the needs of patients and the requirements of a changing health care system.
Keywords: Education; Health and Medicine

Preparing for the Psychological Consequences of Terrorism: A Public Health Strategy - Institute of Medicine (The National Academies Press, 2003)
The Oklahoma City bombing, intentional crashing of airliners on September 11, 2001, and anthrax attacks in the fall of 2001 have made Americans acutely aware of the impacts of terrorism. These events and continued threats of terrorism have raised questions about the impact on the psychological health of the nation and how well the public health infrastructure is able to meet the psychological needs that will likely result. Preparing for the Psychological Consequences of Terrorism highlights some of the critical issues in responding to the psychological needs that result from terrorism and provides possible options for intervention. The committee offers an example for a public health strategy that may serve as a base from which plans to prevent and respond to the psychological consequences of a variety of terrorism events can be formulated. The report includes recommendations for the training and education of service providers, ensuring appropriate guidelines for the protection of service providers, and developing public health surveillance for preevent, event, and postevent factors related to psychological consequences.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

Ensuring Environmental Health in Postindustrial Cities: Workshop Summary - Institute of Medicine (The National Academies Press, 2003)
the Institute of Medicine Roundtable on Environmental Health Science, Research, and Medicine held a regional workshop in Pittsburgh, Pennsylvania, on March 13, 2003. This workshop was a continued outgrowth from the Roundtable's first workshop when its members realized that the challenges facing those in the field of environmental health could not be addressed without a new definition of environmental health--one that incorporates the natural, built, and social environment. The Roundtable realized that the industrial legacy is not unique to Pittsburgh. Other cities around the world have seen their industries disappear, and it is only a matter of time before some of the Pittsburghs of today, such as Wuhan, China, (a sister city) will need to address similar problems. One goal for this IOM Environmental Health Roundtable Workshop is to extract lessons from Pittsburgh's experience in addressing the post-industrial challenge, distilling lessons that might be useful elsewhere.
Keywords: Environment and Environmental Studies; Health and Medicine

Microbial Threats to Health: Emergence, Detection, and Response - Institute of Medicine (The National Academies Press, 2003)
Infectious diseases are a global hazard that puts every nation and every person at risk. The recent SARS outbreak is a prime example. Knowing neither geographic nor political borders, often arriving silently and lethally, microbial pathogens constitute a grave threat to the health of humans. Indeed, a majority of countries recently identified the spread of infectious disease as the greatest global problem they confront. Throughout history, humans have struggled to control both the causes and consequences of infectious diseases and we will continue to do so into the foreseeable future. Following up on a high-profile 1992 report from the Institute of Medicine, Microbial Threats to Health examines the current state of knowledge and policy pertaining to emerging and re-emerging infectious diseases from around the globe. It examines the spectrum of microbial threats, factors in disease emergence, and the ultimate capacity of the United States to meet the challenges posed by microbial threats to human health. From the impact of war or technology on disease emergence to the development of enhanced disease surveillance and vaccine strategies, Microbial Threats to Health contains valuable information for researchers, students, health care providers, policymakers, public health officials. and the interested public.
Keywords: Health and Medicine